2022
DOI: 10.1111/jfpp.16913
|View full text |Cite
|
Sign up to set email alerts
|

Use of a natural antioxidant,Cistus creticusextract, on lipid oxidation and shelf life of ready‐to‐eat beef cocktail sausages

Abstract: The effect of Cistus creticus extract on the quality attributes of cocktail sausages was evaluated. For this purpose (1) the phenolic composition, total phenolic content, total flavonoid content, and antioxidant activity of Cistus extract were determined, and (2) quality parameters, such as lipid oxidation and the shelf life of sausages, were investigated. There were four treatments: a control (0.02% ascorbic acid and 0.05% sodium ascorbate) and Cistus (0.05%, 0.07%, and 0.1%). The radical scavenging activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Regarding oxidative processes, the study by Pernu et al (2020) demonstrated a 15% extension in shelf life by selecting specific temperature combinations and storage conditions. Another study focusing on antioxidants' impact (Pamuk et al, 2022) effectively reduced lipid oxidation, extending the shelf life by 2-3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding oxidative processes, the study by Pernu et al (2020) demonstrated a 15% extension in shelf life by selecting specific temperature combinations and storage conditions. Another study focusing on antioxidants' impact (Pamuk et al, 2022) effectively reduced lipid oxidation, extending the shelf life by 2-3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Cistus creticus is a Mediterranean perennial shrub of the Cistaceae family [6]. It is also known as rock rose and it is widely distributed in Europe, mainly in the Mediterranean region, in West Africa, and in Asia [7,8]. It is mainly native to the island of Crete in Greece [9].…”
Section: Introductionmentioning
confidence: 99%